Kecanduan internet dan kecemasan komunikasi terhadap karakter kerja sama pada mahasiswa - Hidayatullah, Rizki Maulana (PSYCOMEDIA : Jurnal Psikologi, 2023)
This research aims at investigating the correlation of internet addiction and communication anxiety to cooperative character of students. Its subjects were 90 students. The research used the survey method with questionnaire with Likert model scale. Its data were collected through Internet Addiction Test (IAT) with the aspects: of attention centered on internet, longer time spent, less control, agitated feeling during offline, satisfaction-increasing internet, internet as compensation, compulsive behavior, withdrawal, social risk occurrence, and frequent lying. The anxiety scales included unwilling to communicate, avoiding participation, less self-control. The character scales included cooperating with others, raising positive hopes, appreciating inputs and feedbacks, giving encouragements, and cultivating spirits. The data were analyzed by using the multiple linear regression analysis aided with SPSS 19. There was correlation between the two independent variables and the dependent variable